CHARACTERIZATION, BY HIGH RESOLUTION MALDI/FTICR MASS SPECTROMETRY, OF TARA (Caesalpinia Spinosa) HYDROLYSABLE TANNINS - Dávalos, Juan Z. (2017)
We have studied and characterized the structure of hydrolysable tannins of commercial powder tara, performed by means ultra-high-resolution mass spectrometry (MALDI/FT-ICR) without using separation techniques. Our experimental results, supported by computational calculations at DFT/ M05-2X level of theory, show that the identified species are basically oligomeric structures of polygalloyquinic acids, of the (C7H4O4)n(C7H12O6) type, composed by a chain of polygallic esters (depside) linked, via ester bond, to one quinic acid.